Evaluation of FTA card preparation for SSR marker amplification of mEgCIR3607 from mature oil palm leaves - Mohd Asri, Nurul Ain Shahira; Midin, Mohd Razik; Wan Hanafi, Wan Nurhayati (International Islamic University Malaysia, 2025)
The oil palm (Elaeis guineensis) leaves are characterized by high levels of polysaccharides and secondary metabolites, which present significant challenges for effective DNA extraction and Polymerase Chain Reaction (PCR) analysis. The objective of this study is to investigate the applicability of Flinders Technology Associates (FTA) cards to preserve oil palm tissue from mature oil palm leaf for direct PCR. A total of 50 mature oil palm leaf samples were collected from independent smallholder plantations and deposited onto the FTA card. An attempt was made to compare between direct use of FTA card disc and FTA elute as DNA templates for PCR amplification using primer mEgCIR3607. Evaluation of FTA elutes as DNA template on 50 oil palm samples demonstrated successful PCR amplification with high intensity of PCR product. The findings showed that FTA cards effectively preserve DNA from mature oil palm leaves, enabling successful PCR amplification using FTA elute as a DNA template, which demonstrates their suitability for overcoming challenges associated with DNA extraction in Elaeis guineensis.